PARTISIPASI MASYARAKAT DALAM MUSRENBANG DI DESA KEMBIRITAN KECAMATAN GENTENG KABUPATEN BANYUWANGI - Muhammad Asádi; Nasrodin Nasrodin (Department of Islamic Community Development, Faculty of Dakwah,Universitas Islam Ibrahimy Banyuwangi, 2022)
This study aims to apply the principles of decentralization, bottom up, involve the community actively (participatory), local governments are not given the freedom (local discretion) to determine their own regional policies. Participation is a form of active and dynamic action from the community to play its role in development activities. The population in this study were 13 people from Kembiritan village administration, 7 people from the Village Consultative Body (BPD), 10 religious leaders, 8 youth leaders and 9 female leaders. So, the total population of the study amounted to 47 people. In this study, the authors used a non-random sampling technique, namely not all members of the population were given the opportunity to be selected as samples. For more details, the non-random sampling technique that the author uses is the type of porposive sampling. Regarding community participation in the implementation of the Musrenbang this year, it is entered into Step 2 Therapy.